Voltage-based control with a boost converter with a voltage multiplier - Toh, Jia Yue (2015)
The project objective is to design and construct a DC-DC boost converter with a voltage multiplier, voltage-based feedback controller and a sliding mode controller that can attain a high static voltage gain. A voltage-based feedback controller and the sliding mode feedback controller is used to control the converter output voltage. The controller is designed to have the ability to fulfil the robustness and tracking abilities. To monitor the performance of this controller, an open loop test for the converter is conducted followed by a closed-loop test to determine the controller feasibility. Both simulation and experiment result are included to show the feature of the controller. The result shows that it is able to regulate the controller under certain conditions such as specific voltage levels.